Traffic noise and air quality of Singapore expressways - Chng, Joe Wei. (2013)
In view of the limited land space of Singapore but with a high population, residential high-rise buildings were built in very close proximity to major expressways in some instances. This research made use of surveys to obtain the feedbacks of residents living near Pan Island Expressway (PIE) in the Jurong West Estate and those living near Ayer Rajah Expressway (AYE) in the Clementi Estate. The elevated noise level was more of a concern in comparison to the polluted air environment as suggested from the survey responses. Fieldworks were conducted to measure the sound level and air quality of the expressways, being strategically positioned in an adjacent residential building and on an overhead bridge directly above the expressways. Air quality results, particularly the Particulate Matter (PM), pointed towards the fact that both expressway and living environments shared similar substandard air quality of approximately 2.5 to 5 ug/m3 PM 10 concentrations and 1 to 3 ug/m3 for PM 2.5 concentrations. Noise level data revealed that residents experienced an uncomfortable noise level of about 70 dB during traffic peak hours. Comprehensive Modal Emission Model (CMEM), supported by U.S. Environmental Protection Agency, was modified for Singapore’s context and employed to estimate the per second tailpipe emissions of vehicles travelling on PIE and AYE based on a 2-hour period. Based on the investigation results, public awareness should be raised regarding the adverse health effects of the polluted expressways environment. Actions should be taken by the relevant authority to address the concerns of the residents on both the noise and air pollutions.